Solitary osteochondroma of scapula: A case report - Sharma, B D; Sitaula, J; Prajapati, A; Regmi, A P (Journal of Chitwan Medical College, 2017)
Osteochondromas are the most common benign tumours of bone. They are most commonly seen in the metaphyseal regions of long bones (femur, tibia, humerus). The scapula is rarely involved, and very few cases of solitary osteochondroma of scapula have been reported in literature. We present the case of a 17 year old male who presented with pain and limited range of motion of his right shoulder. CT scan revealed an osteochondroma on the dorsomedial surface of the right scapula extending into the ventral surface. Surgical excision was done and histopathological study showed osteochondroma of the scapula.